Modeling the potential distribution of Musa (AAB), cv. 'Bellaco' and Carica papaya under climate change scenarios in the provinces of Jaén and San Ignacio - Cubas Sanchez, Jefferson Anthony (2026)
Plantain (Musa (AAB), cv. 'Bellaco') and papaya (Carica papaya) are key crops for the economy and food security in northwestern Peru; however, the lack of spatially explicit information on their current and future suitability limits agricultural planning and climate change adaptation. This study modeled the current and future potential distribution (2050 and 2070) of both crops in the provinces of Jaén and San Ignacio under the SSP1– 2.6, SSP2– 4.5, and SSP5– 8.5 scenarios, using 262 occurrence records for plantain and 125 for papaya, together with bioclimatic, edaphic, and topographic predictors standardized to a spatial resolution of 1 km. MaxEnt models calibrated with 25-fold cross-validation showed excellent performance (current AUC = 0.922–0.928; projected AUC = 0.957–0.965). The main predictors were elevation (58.97%), precipitation of the coldest quarter (Bio19, 13.39%), and silt content (7.55%) for plantain, and temperature seasonality (Bio4, 82.06%) for papaya. Projections indicate a marked spatial redistribution for both crops. Although between 78.93% and 85.92% of the territory remained in the same suitability class, plantain showed consistently negative net balances across all scenarios, with losses of up to −1690.87 km² under SSP5– 8.5 in 2070. For papaya, some scenarios showed short-term gains in high-suitability areas (up to 26.50% in 2050), but by 2070 net losses predominated, reaching −34.59% under SSP5– 8.5. These findings reveal crop-specific patterns that are overall unfavorable under climate change and provide a spatial basis for crop zoning, territorial prioritization, and the planning of adaptation measures aimed at site selection, crop diversification, and water management.